Analisis Pengaruh Indeks Pembangunan Manusia, Penduduk dan Upah Minimum Kota Terhadap Pengangguran Di Kalimantan Utara Tahun 2017-2020 - Pramono, Wisma Angger; Setyowati, Eni (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
One of the major challenges that is difficult to overcome is the high unemployment rate. Therefore, the aim of this study is to evaluate the impact of the Human Development Index (HDI), population size, and minimum wage on the unemployment rate in North Kalimantan during the period 2017-2020. This study adopts a quantitative approach with multiple regression analysis. The data used are panel data sourced from secondary data provided by the Central Bureau of Statistics (BPS) for the specified period. The results of the study indicate that population size and minimum wage have a positive and significant effect on the unemployment rate, while HDI does not show a significant positive (or negative) effect.